2017
DOI: 10.4254/wjh.v9.i22.959
|View full text |Cite
|
Sign up to set email alerts
|

Low serum albumin predicts early mortality in patients with severe hypoxic hepatitis

Abstract: AIMTo evaluate the incidence, etiology, and predictors of mortality of severe hypoxic hepatitis.METHODSWe used computerized patient records to identify consecutive cases of severe hypoxic hepatitis admitted to a tertiary hospital in Singapore over a one-year period. We defined severe hypoxic hepatitis as elevation of serum transaminases more than 100 times upper limit of normal in the clinical setting of cardiac, circulatory or respiratory failure after exclusion of other causes of hepatitis. We used multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…On the other hand, three different α-HA of amino acid origin (α-hydroxyisovaleric acid, α-hydroxybutyric, and 2,3 dihydroxybutanoic acid) were signi cantly increased in samples from mild and severe COVID-19 patients and positively correlated with CRP and LDH and negatively with SO2 and serum albumin. Reduced levels of this protein have been associated with increased mortality in severe hypoxic hepatitis and COVID-19 [23][24][25] . Similar to glutathione, albumin has an antioxidant activity over ROS control in ischemic and hypoxic liver 26 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, three different α-HA of amino acid origin (α-hydroxyisovaleric acid, α-hydroxybutyric, and 2,3 dihydroxybutanoic acid) were signi cantly increased in samples from mild and severe COVID-19 patients and positively correlated with CRP and LDH and negatively with SO2 and serum albumin. Reduced levels of this protein have been associated with increased mortality in severe hypoxic hepatitis and COVID-19 [23][24][25] . Similar to glutathione, albumin has an antioxidant activity over ROS control in ischemic and hypoxic liver 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a significant difference in AST levels between survivors and non-survivors. One study showed that, among patients with severe hypoxic hepatitis, indicated by mean AST levels of 4896 U/L, low serum albumin levels predicted early mortality 14 . Another study reported a strong relationship between aminotransferase concentrations, including AST, and mortality from liver disease 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Independent predictors of 28‐day mortality included septic shock, cardiogenic shock, history of COPD, metabolic acidosis, raised prothrombin time, and older age. Previous studies in patients with ischemic hepatitis have identified various independent risk factors of mortality: older age, higher ICU severity scores, septic shock, higher international normalized ratio, renal failure, higher bilirubin, higher lactate dehydrogenase, lower albumin, and requirement of vasopressors . However, the study populations have been heterogeneous and typically included ICU patients or patients with severe liver injury with ALT over 3000–4000 IU/L, and none have been conducted on an Australian population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with ischemic hepatitis have identified various independent risk factors of mortality: older age, higher ICU severity scores, septic shock, higher international normalized ratio, renal failure, higher bilirubin, higher lactate dehydrogenase, lower albumin, and requirement of vasopressors. 8,[25][26][27][28] However, the study populations have been heterogeneous and typically included ICU patients or patients with severe liver injury with ALT over 3000-4000 IU/L, and none have been conducted on an Australian population. Our findings have important clinical relevance and suggest that marked ALT derangement warrants urgent investigation to elicit etiology as they confer vastly different mortality risks.…”
Section: Discussionmentioning
confidence: 99%